PENYULUHAN HUMAN TRAFFICKING BAGI KARANG TARUNA KELURAHAN SAMBIROTO KECAMATAN TEMBALANG KOTA SEMARANG - Listyaning Sumardiyani; Sri Suciati; Siti Musarokah (Universitas PGRI Semarang, 2012)
AbstractAdolescence is a period of transition from child to adult. In this transition period, teenagers tend to seek a new identity that is different from their previous identity. The process of search of the new identity makes the teens as a side that are vulnerable to crimes. One of them is human trafficking. Therefore, to anticipate the occurrence of human trafficking crime, Team of IKIP PGRI Semarang held counseling about human trafficking for Local Youth Association of Sambiroto Village, Tembalang, Semarang with the main goal is to make teenagers aware of the dangers of human trafficking and how to prevent this crime. The counseling was held on Saturday March 10, 2012 located at RW 1 Sambiroto Village, Tembalang, Semarang. This event was attended by 48 participants. The materials presented in this activity are the Youth and their problem, Human Trafficking (modus operandi and its main victims), and government efforts and how to prevent human trafficking crime. The methods used in this training include lectures, question and answer, and discussion. The resulting outputs are teenagers of Youth of Sambiroto Village are able to be aware of the dangers of human trafficking crime and know the ways to prevent this crime.Key Words: Counseling, Human Trafficking, Local Youth AssociationAbstrakMasa remaja adalah masa transisi dari anak ke dewasa. Dalam masa transisi, remaja cenderung untuk mencari identitas baru yang berbeda dari identitas mereka sebelumnya. Proses pencarian identitas baru membuat para remaja sebagai sisi yang rentan terhadap kejahatan. Salah satunya adalah perdagangan manusia. Karena itu, untuk mengantisipasi terjadinya kejahatan perdagangan manusia, Tim IKIP PGRI Semarang mengadakan konseling tentang perdagangan manusia untuk Asosiasi Pemuda Sambiroto Tembalang, Semarang dengan tujuan utama adalah untuk membuat remaja waspada bahaya perdagangan manusia dan bahgaimana mencegah tindak kejahatan. Konseling diselenggarakan pada Sabtu 10 Maret 2012 berlokasi di RW 1 Sambiroto, Tembalang, Semarang. Acara ini dihadiri oleh 48 peserta. Materi yang disajikan dalam kegiatan ini adalah mengenai remaja dan masalah mereka. Perdagangan manusia (modus operandi dan korban utamanya), upaya pemerintah dan bagaimana mencegah hal ini. Metode yang digunakan dalam pelatihan ini meliputi ceramah, tanya jawab, dan diskusi. Hasilnya, remaja desa Sambiroto menyadari dan mewaspadi bahaya kejahatan perdagangan manusia dan mengetahui cara untuk mencegah kejahatan ini.Kata Kunci: Konseling, Perdagangan Manusia, Asosiasi Pemuda Lokal